KOMPETENSI, PROFESIONALISME KERJA DAN KINERJA KARYAWAN - Iswanto, Jefri (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Competence, professionalism Employment and Employee Performance. The research objective was to determine the effect of competence and professionalism of the work to employees performance at BPJS Employment Pekanbaru. The study population was all employees BPJS and samples taken as many as 50 people with simple random sampling technique. Data collection techniques were questionnaires, interviews and observation. Analysis of data using multiple linear regression. The result showed that the competence and professionalism simultaneously significant effect on employee performance with the correlation (r) 0.760. R 0.760 meaningful contribution with competence and professionalism in the performance of employees is only 57.8%, while the remaining 42.2% is determined by other factors.